A clinical observational study on second-trimester abortion - R., Geetha Lakshmi; Pranavi, Bommireddy; George, Neethu; Saraswathi, K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Second-trimester abortion is an important component of the comprehensive women’s health care. Data’s regarding second-trimester abortion is still under-reporting. Though the percentage of induced second-trimester abortion is low, its morbidity is higher than the first-trimester induced abortion. The abortion related mortality usually increases with the age of gestation. Methods: A retrospective observational study was conducted in the department of obstetrics and gynecology at Sree Balaji Medical College and Hospital, Chennai, over a period of one year. The data were collected from the medical case records and we have analyzed on the epidemiology, etiologies, complications and the methods of second- trimester abortion using statistical analysis. Results: In this study, there was no standard regimen of mifepristone and misoprostol were used for second-trimester abortion. The dosages were varied based on the gestational age of pregnancy. As the gestational age progresses, the amount of misoprostol required for the induction of second trimester abortion decreases and the difference is statistically significant. There was no reported case of rupture uterus, but varied complications such as post-abortal hemorrhage, retained placenta, need for blood transfusion, uterine perforation and one maternal death were reported during the study period. Conclusions: In order to reduce the morbidity and mortality of second trimester abortion, more policies and monitored services have to be rendered by the health system. Data regarding the second trimester abortion have to be improved.